2018
DOI: 10.18203/2320-6012.ijrms20184045
|View full text |Cite
|
Sign up to set email alerts
|

New onset diabetes after transplantation (NODAT) in renal transplant recipients: a study from tertiary care center in Kashmir, India

Abstract: Background: New onset diabetes after transplantation (NODAT) is a common entity in the post-transplant period after several types of organ transplants like kidney, liver heart and lungs. NODAT is a common complication after solid organ transplantation and has been reported to have an adverse impact on patient and allograft outcomes. Risk stratification and intervention to minimize risk should be an integral part of management of transplant recipients.Methods: A total of 100 patients who underwent renal transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Similar observations were reported in populations of Malaysia [33] and Singapore. [38] In Indian studies from Kerala [41] and Kashmir, [42] significance was not found in BMI between NODAT versus non-NODAT groups which is similar to the present study. The previous studies have reported that NODAT is associated with obesity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar observations were reported in populations of Malaysia [33] and Singapore. [38] In Indian studies from Kerala [41] and Kashmir, [42] significance was not found in BMI between NODAT versus non-NODAT groups which is similar to the present study. The previous studies have reported that NODAT is associated with obesity.…”
Section: Discussionsupporting
confidence: 89%
“…In a study from Kashmir among renal transplant recipients, higher means levels of calcium and lower mean levels of phosphorus have been reported in NODAT subjects than normal individuals. [42] conclusIon The present study revealed that older age (above 40) to be significant factor for the development of NODAT. Higher levels of creatinine, urea, and uric acid in serum might be associated with the development of NODAT and could also be the important markers for the assessment of kidney function in renal transplant recipients.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation